2018
DOI: 10.1111/lam.13072
|View full text |Cite
|
Sign up to set email alerts
|

Stress survival islet 1 contributes to serotype-specific differences in biofilm formation in Listeria monocytogenes

Abstract: Listeria monocytogenes has a significant impact on the food industry by forming biofilms on food-processing equipment. Tandem analysis of whole-genome sequencing data with biofilm data from 166 environmental and food-related L. monocytogenes isolates has revealed serotypic and genetic factors that strongly correlate with adherence and biofilm formation, such as lineage, plasmid harbourage, a three-codon deletion in inlA and the presence of the stress survival islet 1 (SSI-1). Strains from serotype 1/2b, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…These findings were consistent with previous studies reporting that serogroup IVb strains demonstrated a lower capacity for biofilm formation and that CC9 and CC121 were able to make more biofilm than CC1 and CC2 [4,61]. Moreover, Keeney et al [61] reported that the presence of SSI-1 was strongly correlated with biofilm formation and according to Franciosa et al [15], the PMSC mutation in the inlA gene was associated with enhanced biofilm levels when compared to the wild type inlA. Further studies investigated at the same time the influence of SSI-1 and a truncated inlA protein, finding that they were both significantly associated with increased levels of biofilm [14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were consistent with previous studies reporting that serogroup IVb strains demonstrated a lower capacity for biofilm formation and that CC9 and CC121 were able to make more biofilm than CC1 and CC2 [4,61]. Moreover, Keeney et al [61] reported that the presence of SSI-1 was strongly correlated with biofilm formation and according to Franciosa et al [15], the PMSC mutation in the inlA gene was associated with enhanced biofilm levels when compared to the wild type inlA. Further studies investigated at the same time the influence of SSI-1 and a truncated inlA protein, finding that they were both significantly associated with increased levels of biofilm [14].…”
Section: Discussionsupporting
confidence: 93%
“…Statistically significant differences were found in the biofilm production by different Lm serogroups (IIa, IIb and IVb), with serogroups IIa and IVb presenting the highest and lowest values respectively. These findings were consistent with previous studies reporting that serogroup IVb strains demonstrated a lower capacity for biofilm formation and that CC9 and CC121 were able to make more biofilm than CC1 and CC2 [4,61]. Moreover, Keeney et al [61] reported that the presence of SSI-1 was strongly correlated with biofilm formation and according to Franciosa et al [15], the PMSC mutation in the inlA gene was associated with enhanced biofilm levels when compared to the wild type inlA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While our study showed that the previously reported stress survival islets 1 and 2 (SSI-1 and -2, respectively) were associated with clusters and subclusters, we were not able to identify clear growth or stress response phenotypes associated with the presence of these islets. SSI-1 was detected among all cluster 3 isolates; this islet has been suggested to contribute to growth under low pH (pH 4.8), high salt (7.5% NaCl), and a combination of both (pH 5.2 and 5% NaCl) (8) as well as to biofilm formation at 30°C (37) and salt-induced nisin resistance (38). While 34 of 42 isolates in this study harbored SSI-1, only 3 of 12 isolates from a cold-smoked processing facility in Ireland harbored this islet (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several genes may regulate bio lm development, allowing bacterial survival under adverse environmental conditions (Keeney et al 2018). Despite being also probably related to L. monocytogenes pathogenicity, the molecular mechanisms responsible for the expression of bio lm related genes are not completely understood (Lemon et al 2007;Bonsaglia et al 2014;Nowak et al 2017).…”
Section: Introductionmentioning
confidence: 99%